The dynamics of legal politics in resolving regional policy conflicts - Judijanto, Loso; Datumula, Sarpika (Ipso Jure, 2024)
Regional policy conflicts often arise due to a mismatch between community needs and government policies. This imbalance reflects the complex dynamics involving various parties, such as local governments, legislatures and communities, with different interests. In this context, legal politics plays an important role as a framework for creating fair and sustainable solutions. Law No. 23/2014 and Law No. 30/2014 emphasize community participation, accountability and transparency in policy conflict resolution. However, implementation in the field is often constrained by political resistance, limited resources, and unfamiliarity with legal principles. This research uses a descriptive method with a qualitative approach through documentation studies, interviews, and observations. The results show that inclusivity, cross-sector collaboration, and a flexible approach to local needs are the main keys to overcoming policy conflicts. Alternative mechanisms, such as mediation and arbitration, offer a more peaceful resolution than litigation. Transparency in the policy process is also important to increase legitimacy and public trust. With the integration of community needs, national legal principles, and adaptive regulations, legal politics can be a strategic tool to resolve local policy conflicts. This approach supports harmonious sustainable development, creates social stability, and enhances justice at the local level.